International R&D cooperation between low-tech SMEs: the role of cultural and geographical proximity - Teixeira, A. A. C.; Santos, P.; Brochado, A. (European Planning Studies, 2008)
Although there is a considerable amount of empirical evidence on inter-firm collaborations within technology-based industries, there are only a few works focussing on R&D cooperation by low-tech firms, especially small and medium-sized enterprises (SMEs). Providing further and new evidence based on a recently built database of CRAFT projects, this study analyses the relationship between technology and proximity in international R&D networks using HOMALS and statistical cluster techniques. The resulting typology of international cooperative R&D projects highlights that successful international cooperative R&D projects are both culturally/geographically closer and distant. Moreover, and quite interestingly, geographically distant projects are technologically more advanced whereas those located near each other are essentially low-tech. Such evidence is likely to reflect the tacit-codified knowledge debate boosted recently by the information and communication technology (ICT) "revolution" emphasized by the prophets of the "Death of Distance" and the "End of Geography".